2012
DOI: 10.1177/1049731512451060
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Research and Practice Evaluation Skills to Graduate Social Work Students

Abstract: Objective: The authors examined outcomes of a graduate course on evaluating social work practice that required students to use published research, quantitative measures, and single-system designs in a simulated practice evaluation project. Method: Practice evaluation projects from a typical class were analyzed for the number of research references cited, type of client, goals or problems, measures, interventions, single-system designs, and outcomes. Results: More than half of the students conducted selfimprove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The writing tests in sessions 3 and 12 were designed to specifically target a subset of skills needed by students before they write their first journal article, and reflect the fact that students can struggle with academic writing if their previous experience is limited to lab reports. , The journal paper assessment using a template from a real publication has been used successfully in previous studies. , Students had learned to use software such as EndNote for referencing and ChemDraw to produce publication-quality figures for their articles in a previous module.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The writing tests in sessions 3 and 12 were designed to specifically target a subset of skills needed by students before they write their first journal article, and reflect the fact that students can struggle with academic writing if their previous experience is limited to lab reports. , The journal paper assessment using a template from a real publication has been used successfully in previous studies. , Students had learned to use software such as EndNote for referencing and ChemDraw to produce publication-quality figures for their articles in a previous module.…”
Section: Discussionmentioning
confidence: 99%
“…1 Research-based experiments have also been shown to impart a greater understanding of the nature of science to students, compared to traditional teaching experiments, 2 and research experiences are thought to 30 increase both retention and graduation rates. 3 Traditionally, students developed their research skills during a placement or project in an academic research group via a kind of peer-guided osmosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Social workers select and use appropriate methods for evaluation of outcomes; critically analyze, monitor and evaluate intervention processes and outcomes; and apply evaluation findings to improve practice effectiveness. (CSWE, 2013, p. 7) There have been attempts, although few and far between, to propose effective ways of teaching program evaluation to social work students and to evaluate the short-term impact of such efforts on students (Baker, Hudson, & Polio, 2011;Wong & Vakharia, 2012). The impact on the professional practice of students who attended such courses has, to the best of our knowledge, not been evaluated.…”
Section: Introductionmentioning
confidence: 99%